2022
DOI: 10.1002/ijgo.14122
|View full text |Cite
|
Sign up to set email alerts
|

The association between gestational weight gain and perinatal outcomes among underweight women with twin pregnancy in Japan

Abstract: The development of artificial reproductive technology has led to an increase in the prevalence of twin pregnancies worldwide. The rate of twin pregnancies has doubled in the United States since 1970s 1 and has increased by 1.3 times from 1983 to 2004, while this rate has been decreasing since 2005 in Japan. 2 Compared with singleton pregnancies, twin pregnancies are associated with higher risks of adverse outcomes (fetal growth restriction, preterm birth, and preeclampsia). 1 Therefore, understanding how pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…In the present study, we found that a high GWG additionally increased HDP in twin pregnancies in agreement with previous findings by others 6,7 . Maeda et al recently confirmed this association even in underweight women 18 . Since we divided our study cohort into three groups of GWG using the same range for all BMI groups, our cut‐off for low GWG in obese women was higher than suggested by Lipworth et al 11 But even using this cut‐off, low GWG was significantly associated with increased risks for stillbirth and NICU admissions in obese women.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In the present study, we found that a high GWG additionally increased HDP in twin pregnancies in agreement with previous findings by others 6,7 . Maeda et al recently confirmed this association even in underweight women 18 . Since we divided our study cohort into three groups of GWG using the same range for all BMI groups, our cut‐off for low GWG in obese women was higher than suggested by Lipworth et al 11 But even using this cut‐off, low GWG was significantly associated with increased risks for stillbirth and NICU admissions in obese women.…”
Section: Discussionsupporting
confidence: 94%
“… 6 , 7 Maeda et al recently confirmed this association even in underweight women. 18 Since we divided our study cohort into three groups of GWG using the same range for all BMI groups, our cut‐off for low GWG in obese women was higher than suggested by Lipworth et al 11 But even using this cut‐off, low GWG was significantly associated with increased risks for stillbirth and NICU admissions in obese women. We were able to assess the outcomes for underweight women and for rare outcomes such as stillbirth and perinatal mortality due to our larger cohort.…”
Section: Discussionmentioning
confidence: 89%
“…In a previous Chinese study, twin-pregnant women who gained weight above guidelines were more likely to have LGA >90th percentile and less likely to have LBW <2,500 g, 10 whereas preeclampsia was more frequent among excessive GWG twin-pregnant women, which was similar to our results. 10 14 28 29 30 It may be that EGWG leads to an increased maternal systemic inflammation response, and the resulting damage to vascular endothelial cells may cause preeclampsia. 31 Therefore, GWG would potentially be a preventable risk factor for preeclampsia.…”
Section: Discussionmentioning
confidence: 99%